The increase in hemoglobin concentration with altitude differs between world regions and is less in children than in adults - Mairbäurl, Heimo; Kilian, Samuel; Seide, Svenja; Muckenthaler, Martina; Gassmann, Max; Benedict, Rukundo K. (HemaSphere, 2023)
To compensate for decreased oxygen partial pressure, high-altitude residents increase hemoglobin concentrations [Hb]. The elevation varies between world regions, posing problems in defining cutoff values for anemia or polycythemia. The currently used altitude adjustments (World Health Organization [WHO]), however, do not account for regional differences. Data from The Demographic and Health Survey (DHS) Program were analyzed from 32 countries harboring >4% of residents at altitudes above 1000 m. [Hb]-increase, (ΔHb/km altitude) was calculated by linear regression analysis. Tables show 95% reference intervals (RIs) for different altitude ranges, world regions, and age groups. The prevalence of anemia and polycythemia was calculated using regressions in comparison to WHO adjustments. The most pronounced Δ[Hb]/km was found in East Africans and South Americans while [Hb] increased least in South/South-East Asia. In African regions and Middle East, [Hb] was decreased in some altitude regions showing inconsistent changes in different age groups. Of note, in all regions, the Δ[Hb]/km was lower in children than in adults, and in the Middle East, it was even negative. Overall, the Δ[Hb]/km from our analysis differed from the region-independent adjustments currently suggested by the WHO resulting in a lower anemia prevalence at very high altitudes. The distinct patterns of Δ[Hb] with altitude in residents from different world regions imply that one single, region-independent correction factor for altitude is not be applicable for diagnosing abnormal [Hb]. Therefore, we provide regression coefficients and reference-tables that are specific for world regions and altitude ranges to improve diagnosing abnormal [Hb].
Gesehen am 19.05.2023